Free Vascularized Fibula Graft for Staged Reconstruction of Infected Humerus Nonunions. Issue 5 (May 2023) - Lefebvre, Rachel; Bougioukli, Sofia; Marecek, Geoffrey; Howard, Mark; Cohen, Landon; Stevanovic, Milan
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objective: To evaluate the union rate and rate of postoperative complications in patients with septic nonunions of the humerus after a two-stage reconstruction using a free vascularized fibula graft. Design: Retrospective case series. Setting: Academic, tertiary referral center. Patients/Participants: Adult patients with staged reconstruction for infected nonunion of the humerus with at least 2 years follow-up after vascularized fibula graft transfer. Intervention: First, infected nonunion debridement with antibiotic spacer and external fixator placement. After antimicrobial treatment, free vascularized fibula transfer with internal fixation. Main Outcome Measurements: Time to union, pain, affected extremity range of motion, and function. Results: 10 patients with septic humerus nonunion treated with staged reconstruction using a free vascularized fibula graft, with a mean follow-up of 32.3 months were included. After the two-stage reconstruction using a free fibula, radiographic union was achieved in 6/10 patients, with a mean time to union of 19.9 weeks. The remaining 4 patients required an additional procedure with graft augmentation and/or implant revision. After the revision procedure, union was noted in 3/4 patients, 21 weeks postoperatively. Mean patient visual analog scale pain scores improved from 5.8 preoperatively to 0.9 at final follow-up ( P = 0.02). Postoperatively, mean elbow flexion was 110 ± 20 degrees and extension 15 ± 7.5 degrees. Conclusion: A two-stage reconstruction using a free fibula graft can be used in patients with septic nonunions of the humerus in the setting of multiple failed prior surgeries and compromised local biology. Additional procedures may be needed in some to achieve final union. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.